Human Adaptation of Ebola Virus during the West African Outbreak - Urbanowicz, Richard A; McClure, C Patrick; Sakuntabhai, Anavaj; Sall, Amadou A; Kobinger, Gary; Müller, Marcel A; Holmes, Edward C; Rey, Félix A; Simon-Loriere, Etienne; Ball, Jonathan K (Cell, 2016)
The 2013-2016 outbreak of Ebola virus (EBOV) in West Africa was the largest recorded. It began following the cross-species transmission of EBOV from an animal reservoir, most likely bats, into humans, with phylogenetic analysis revealing the co-circulation of several viral lineages. We hypothesized that this prolonged human circulation led to genomic changes that increased viral transmissibility in humans. We generated a synthetic glycoprotein (GP) construct based on the earliest reported isolate and introduced amino acid substitutions that defined viral lineages. Mutant GPs were used to generate a panel of pseudoviruses, which were used to infect different human and bat cell lines. These data revealed that specific amino acid substitutions in the EBOV GP have increased tropism for human cells, while reducing tropism for bat cells. Such increased infectivity may have enhanced the ability of EBOV to transmit among humans and contributed to the wide geographic distribution of some viral lineages.